Influencing Factors of Double Roll Coating Ratio of Reconstituted Tobacco by Papermaking - Huifan Li; Yuxin Liu; Jing Liu; Gaofeng Dong; Zhongren Li; Wenjun Zhang (BioResources)
To investigate and elucidate the influencing factors and laws of double-roll coating ratio (CR) for papermaking reconstituted tobacco and to assess the effectiveness of CR in characterizing the finished product's hot water soluble (HWS) content, base sheet (BS) specimens of reconstituted tobacco with varying bone-dry basis weights and moisture contents were prepared. These sheets were then coated with different physical indices of coating liquids using a small double-roll coater at different sheet speeds. Subsequently, the CR and HWS content of the finished product were analyzed. The results showed that when the viscosity of the coating liquid was > 280 mPa·s, the moisture content of the BS should be maintained between 18% and 22%, and the speed of the BS should be > 120 m/min; when the viscosity of the coating liquid is < 280 mPa·s, the moisture content of the BS should be maintained between 14% and 18%, and the speed of the BS should be > 120 m/min, so that higher HWS can be obtained in finished products. The bone-dry basis weight of the BS should be kept between 40 and 60 g/m2. The suspension solid content of coating liquid should be <  9.5%.